(untitled) (Revista Direitos Humanos e Democracia, 2025)
This study investigates the adaptive capabilities of the company JSOMA, operating in a Public-Private Partnership (PPP) in the Brazilian prison system, focusing on the Modulated State Penitentiary of Ijuí-RS. This is a single, exploratory, descriptive and qualitative case study, with a longitudinal and historical approach, based on the dimensions of organizational change analysis proposed by Pettigrew, Ferlie and McKee (1992) and on the direct research procedures of Mintzberg (1979). Data collection was carried out through semi-structured interviews, covering critical events between 2019 and 2024. The analysis highlights three strategic periods in which dynamic capabilities, especially the adaptive one, according to Wang and Ahmed (2007), emerged as an essential element for organizational effectiveness and sustainability. As its main theoretical contribution, the study proposes transferable analytical categories - based on analytical generalization (Yin, 2010) - that can broaden understanding and be explored in future research on the development of adaptive capabilities in interorganizational arrangements in a context of high institutional complexity.